Ni-Co Alloy and Multisegmented Ni/Co Nanowire Arrays Modulated in Composition: Structural Characterization and Magnetic Properties - Méndez, Miguel; González, Silvia; Vega, Víctor; Teixeira, Jose; Hernando, Blanca; Luna Criado, Carlos; Prida, Víctor M. (2017)
Abstract: Design of novel multisegmented magnetic nanowires can pave the way for the next generation of data storage media and logical devices, magnonic crystals, or in magneto-plasmonics, among other energy conversion, recovery, and storage technological applications. In this work, we present a detailed study on the synthesis, morphology, structural, and magnetic properties of Ni, Co, and Ni-Co alloy and multisegmented Ni/Co nanowires modulated in composition, which were grown by template-assisted electrodeposition employing nanoporous anodic aluminum oxide as patterned templates. X-ray diffraction, and scanning and high-resolution transmission electron microscopies allowed for the structural, morphological, and compositional investigations of a few micrometers long and approximately 40 nm in diameter of pure Ni and Co single elements, together with multisegmented Ni/Co and alloyed Ni-Co nanowires. The vibrating sample magnetometry technique enabled us to extract the main characteristic magnetic parameters for these samples, thereby evaluating their different anisotropic magnetic behaviors and discuss them based on their morphological and structural features. These novel functional magnetic nanomaterials can serve as potential candidates for multibit magnetic systems in ultra-high-density magnetic data storage applications. Keywords: nanoporous alumina template; electrodeposition; crystalline structure; magnetic anisotropy; nanowire